2014
DOI: 10.1186/1880-5981-66-134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the global occurrences of ionospheric irregularities and deep atmospheric convective clouds in the intertropical convergence zone (ITCZ)

Abstract: To study the seeding mechanism of ionospheric irregularity occurrences, a correlation study has been carried out between the global monthly/latitudinal (m/l) distributions of irregularity occurrences and the deep atmospheric convective clouds in the intertropical convergence zone (ITCZ) indicated by the outgoing longwave radiation (OLR) measurements. Seven longitude sectors -the African, Indian, West Pacific, Central Pacific, East Pacific, South American, and Atlantic sectors -are selected to study the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
(52 reference statements)
1
26
2
Order By: Relevance
“…In earlier studies on the statistical correlation between ionospheric bubbles and ITCZ, the daily OLR values were used [e.g., McClure et al , ; Tsunoda , ; Su et al , ]. Here we adopt a similar way as that used in the earlier studies to investigate if there is any relationship between the significantly enhanced bubble generation over Kototabang and the ITCZ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies on the statistical correlation between ionospheric bubbles and ITCZ, the daily OLR values were used [e.g., McClure et al , ; Tsunoda , ; Su et al , ]. Here we adopt a similar way as that used in the earlier studies to investigate if there is any relationship between the significantly enhanced bubble generation over Kototabang and the ITCZ.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 (right bottom) shows the longitudinal variation of the mean occurrence rate of OLR within ±5°magnetic latitude. Note that the OLR (<190) occurrence rate is also shown since Su et al [2014] suggested that a well-defined threshold of OLR (with lower values) would help to assure the GW occurrence. It is evident from the panel that for both thresholds (190 and 205), the OLR occurrence rate is clearly higher at Kototabang longitude than at Sanya longitude.…”
Section: 1002/2016gl068145mentioning
confidence: 99%
See 1 more Smart Citation
“…Although many research studies on the ionosphere have been conducted based on geographic coordinates (Su et al 2014;Talaat and Zhu 2016), some ionospheric characteristics, especially north-south asymmetry, are also investigated compared with geomagnetic coordinates (Geonhwa et al 2004(Geonhwa et al , 2005Weihua and Jiaping 2015). Many geospace phenomena, including ionospheric currents, are highly organized by the Earth's main geomagnetic field.…”
Section: Hemispheric Asymmetry In Geomagnetic Coordinatesmentioning
confidence: 99%
“…As early as in 1950s, Bauer (1958), for the first time, observed ionospheric signature in the passage of hurricanes and found that maximum enhancement in foF2 occurred when hurricanes were closest to the observation station. Also, Huang et al (1985) In fact, most of the previous studies have been reported about two responsible mechanisms which affect the ionosphere mostly during different lower atmospheric meteorological phenomena, these are: (i) Electrical and Electromagnetic process (Harrison et al 2010, Sorokin et al 2005, and (ii) Upward propagating waves generated in the neutral atmosphere (Lastovicka, 2006;Su et al 2014), such as the planetary waves, the tidal waves and the AGWs (Killeen and Johnsson, 1995;Bhattacharya and Das, 2013). However, the former option is out of the scope of this study and ionospheric signature due to the evolution in AGWs is of our main concern.…”
Section: Introductionmentioning
confidence: 99%